Investigation on the Resources which Provide the Differentiation in Strategies that Lead to the Heterogeneity of Fee-based Income of Kasikorn Bank Focus on Retail Banking Business – A Resources Based View - Promburee, Pichayut (2016)
The purpose of this research is to identify the resources which are the sources of Kasikorn Bank’s strategy that allow the differentiation on the strategy and performance, comparing to its competitors. Resource-based view, traditional and universal banking, organisational culture and innovation were studied as literature reviews. The reviews were studied in order to acquire the clear understanding of the theory and contents. The data for the study were collected through the purposive sampling in-depth interview from thirteen interviewees. The researcher found that reputational resources, human resources, organisational culture, structure, and working mechanism are the resources that provide sustainable competitive advantages to Kasikorn Bank. In addition, human resources individually do not provide the sustainable competitive advantages. The resources required the support of other resources to sharpen itself. By the investigation, it seems that the CEO of Kasikorn Bank is a key person of the differentiation of the resources. The research concludes that the length of the CEO or President appointed on the position and average age of Board of Directors will shape higher efficiency culture, structure and system which affect to the organisational innovation, working style and performance. The result of the study provides the useful model of the change from traditional banking to innovative universal banking which can be used as a basis of the organisational reforming.